2015
DOI: 10.1113/jp270093
|View full text |Cite
|
Sign up to set email alerts
|

Daily heat stress treatment rescues denervation‐activated mitochondrial clearance and atrophy in skeletal muscle

Abstract: Key pointsr Traumatic nerve injury or nerve disease leads to denervation and severe muscle atrophy. Recent evidence shows that mitochondrial loss could be a key mediator of skeletal muscle atrophy.r Here, we show that daily heat stress treatment rescues denervation-induced loss of mitochondria and concomitant muscle atrophy.r We also found that denervation-activated autophagy-dependent mitochondrial clearance (mitophagy) was suppressed by daily heat stress treatment. The molecular basis of this observation is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 55 publications
3
55
3
Order By: Relevance
“…In contrast, we found that heat stress attenuates denervation-activated mitophagic flux 42) . Mitophagy is roughly divided into two processes of 1) ubiquitination of mitochondrial proteins (i.e.…”
Section: Heat Stress Attenuates Denervation-activated Mitophagic Fluxcontrasting
confidence: 50%
See 4 more Smart Citations
“…In contrast, we found that heat stress attenuates denervation-activated mitophagic flux 42) . Mitophagy is roughly divided into two processes of 1) ubiquitination of mitochondrial proteins (i.e.…”
Section: Heat Stress Attenuates Denervation-activated Mitophagic Fluxcontrasting
confidence: 50%
“…Since denervation-induced mitochondrial loss can be explained by a decrease in PGC-1α, we examined the possibility that heat stress attenuates the reduction of PGC-1α by denervation. As a result, heat stress did not suppress the decrease of PGC-1α due to denervation 42) . In addition, although glucose transporter 4 (GLUT4) and fatty acid transporter/cluster of differentiation 36 (FAT/CD36), targets of PGC-1α other than mitochondria, also showed a decrease due to denervation, an improvement effect by heat stress was not observed 42) .…”
Section: Heat Stress Attenuates Mitochondrial Loss Due To Experimentamentioning
confidence: 95%
See 3 more Smart Citations